The resilience of Cambodia’s music through darkness: An oral history of the Khmer Rouge regime and its adverse effects on the legacy of Cambodia’s golden era of music. - Justin Kdep (The Young Researcher, 2023)
In the early 1960’s, Cambodia was introduced to its “golden era” of music. Unfortunately, Pol Pot and the Khmer Rouge would overthrow Cambodia’s Government, ending the reign of Cambodia’s golden era, and leading to a 5-year regime filled with brutality, torment, and thousands of mass atrocities. The purpose of this study was to seek a better understanding of how the legacy of Cambodia’s golden era has been impacted by the events of the Khmer Rouge regime. In order to preserve the voices of the survivors of the regime, oral history interviews were conducted with ten different survivors of the Khmer Rouge regime. The outcome of this study revealed that music from the golden era was significant to helping those who have endured such tragedy, by providing emotional support. This music has helped many survivors heal from their past traumas while also simultaneously helping to reminisce on their past.